Maturação de sementes de aveia-preta (Avena strigosa Schreb). I. Maturidade do campo - Nakagawa, J.; Cavariani, Cláudio [UNESP]; MACHADO, JR (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1994)
The present work aimed to define the field maturity of Avena strigosa Schreb seeds cv. Comum. Three experiments were carried out in field conditions during 1986, 1987 and 1989 in Botucatu, SP, Brazil. The sowings were made in May. The characteristics evaluated were: panicles and spikelet aspects, the weight of the dry matter of 100 seeds with and without glumes, the seed moisture, the percentage of germinated seeds (sum of normal + abnormal seedlings), the percentage of germination and vigor (first count of germination test). Based on the dry matter accumulation and the gemination percentage of the seeds, it was concluded that the field maturity of the seeds was reached around 28 and 3 5 days after 100% of panicles emergence of the field. At this stage, the field presented a few percentage of particles (+/- 20%) not yet all yellowish, with spikelets at semi-hard stage and the seeds with 20 to 30% of moisture.
Maturation of avena-strigosa schreb seeds .1. field maturity
Keywords: SEED GERMINATION; DRY MATTER WEIGHT OF 100 SEEDS; PANICLE ASPECT; SPIKELET ASPECT